A Magneto‐Reflectivity Study of CuGaSe2 Single Crystals. Issue 2 (29th October 2018) - Yakushev, Michael V.; Mudryi, Alexander V.; Faugeras, Clement; Martin, Robert W.
Abstract : CuGaSe2 single crystals are studied using magneto‐reflectivity at 4.2 K in magnetic fields B up to 20 T. The A and B free excitons, observed in the optical reflectivity spectra, blue shift with increasing B . A low‐field perturbation approach within the anisotropic hydrogenic model is used to fit the dependence of the spectral position of these excitons on B . The A and B exciton reduced masses of 0.115  m 0 and 0.108  m 0 ( m 0 is the free electron mass), Rydbergs of 12.9 and 12.2 meV, Bohr radii 5.08 and 5.4 nm, and effective hole masses of 0.64 m 0 and 0.48  m 0, respectively, are determined. Abstract : The dependence of the spectral position of the A and B free excitons on the strength of magnetic fields in magneto‐reflectivity spectra of CuGaSe2 single crystals is analyzed using a low‐field perturbation approach within the hydrogenic model. The reduced masses, Rydbergs, Bohr radii, and effective hole‐masses of these excitons are determined.